Análise de modelos de maturidade para medição da implementação do building information modeling (BIM) - Lima, Luciana de Oliveira (2019)
BIM, also known in Brazil as “Modelagem da Informação da Construção” (MIC), is aprocess that has been classified as a disruptive innovation because it deeply modifies the technical solutions of an organization. The implementation of any new technology, however, is fraught with challenges and BIM is no exception. In this way, it is essential that the use of BIM is evaluated so that it is possible to control and measure the development of the BIM deployment. Through an evaluation that has a consistent set of metrics, organizations come to know their own competencies, and are able to compare their results with other companies in the market. Thus, in the last decade at least 16 maturity models have been developed internationally, but there are no studies that prove the applicability of these tools in the Brazilian context. The purpose of this research is to evaluate the applicability of maturity models in the context of Brazilian organizations, as well as to suggest the most adequate models that can be incorporated by the “Estratégia BIM BR” of the National Government, whose purpose is to promote innovation in the Brazilian construction. The methodology employed was based on the use of comparative procedures and field studies. The first one was used to compare eight major maturity models for which three were selected - BIM Assessment Profile, BIM Maturity Matrix and VDC Scorecard - and analyzed, through the analysis of the metrics and the basic principles of each one. In the second procedure, the three models were applied in nine AEC organizations of Curitiba-PR, where the application characteristics of each one were distinguished, besides identifying the degree of BIM maturity of the companies and projects analyzed. From the applications and analyzes, the quality characteristics of the models in question were distinguished. The results show that the three models mainly measure procedural issues besides techniques and people. The BIM Assessment Profile, a basic, simple and flexible quality model, has proved to be more appropriate in organizations that are in the early stages of BIM adopting, or that have stagnant processes. The BIM Maturity Matrix, which is also basic, simple and flexible, is suitable for small or medium sized organizations with well defined sectors. The VDC Scorecard is the most complex, since it presents basic, descriptive and prescriptive characteristics, besides being less flexible, but it is the most comprehensive. It is indicated to evaluate large projects. It was concluded that the maturity models studied can be used in the Brazilian context, but the BIM Assessment Profile is the most appropriate model for the Brazilian AEC organizations.